2018
DOI: 10.1021/acs.jafc.8b01577
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride Structure Modulates Gastrointestinal Digestion Fates of Lipids: A Comparative Study between Typical Edible Oils and Triglycerides Using Fully Designed in Vitro Digestion Model

Abstract: Three typical edible oils (palm oil, PO; leaf lard oil, LO; rapeseed oil, RO) and triacylglycerols (TAGs) (glycerol tripalmitate, GTP; glycerol tristearate, GTS; glycerol trioleate, GTO) were selected to conduct digestion experiments using fully designed in vitro digestion model. The evolutions in mean particle diameter, ζ-potential, and microstructural changes during different digestion stages were investigated. Free fatty acid (FFA) release extent and kinetics were monitored by pH-Stat method. The particle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 46 publications
2
39
2
Order By: Relevance
“…A three-stage (oral, gastric, and intestinal) in vitro digestion model was established based on previous reports with slight modifications [32] , [33] , [34] . The first step was the preparation of simulated digestive juices for each digestion stage.…”
Section: Methodsmentioning
confidence: 99%
“…A three-stage (oral, gastric, and intestinal) in vitro digestion model was established based on previous reports with slight modifications [32] , [33] , [34] . The first step was the preparation of simulated digestive juices for each digestion stage.…”
Section: Methodsmentioning
confidence: 99%
“…The FAMEs were obtained by collecting the upper layer solution, and then filtered through a 0.45 μm organic membrane filter. The fatty acid composition analysis protocols were developed by our own laboratory, which had been reported in detail in a recent paper (Ye, Cao, Liu, Cao, & Li, ). Briefly, 1.0 μL of the FAMEs was injected into GC, with nitrogen carrier gas at a flow rate of 1 mL/min and split in a ratio of 1:100.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it has also been reported that hydrolysis is more efficient the smaller the number of carbon atoms of the acyl groups [ 6 , 27 , 29 , 33 ]. For this reason, the tendency of palmitic group to hydrolyze should be greater than that of stearic group, although some authors find no difference between them [ 32 , 34 , 35 ]. Compositional data of the oils involved in this study given in Table 2 do not permit an analysis of some of the above-cited considerations.…”
Section: Resultsmentioning
confidence: 99%